Water stress, vermiculite and cultivars III. Effect on nitrogen balance in the soil-plant system in rice - Stone, Luis Fernando; Libardi, Paulo Leonel; Reichardt, Klaus (Pesquisa Agropecuaria Brasileira, 2014)
The effect of four irrigation levels, two vermiculite treatments and three rice cultivars (Oryza sativa L.) (IAC 47, IRAT 13 and IET 1444) on the nitrogen balance in the soil-plant system was studied in a greenhouse experiment. The treatments included the irrigation levels corresponding to 55%, 70%, 85% and 100% of maximum evapotranspiration with and without vermiculite incorporation in the soil at 10% concentration on volume basis. Water stress decreased rice plant uptake of nitrogen derived from the fertilizer. The incorporation of vermiculite into the soil also decreased the uptake, probably due the ammonium fixation. The cv. IET 1444 absorbed more nitrogen than the other cultivars tested. About 10% to 20% of the nitrogen supplied as fertilizer remained in the soil. While the plant uptake corresponded to 67% to 9O% in the absence of vermiculite, it was reduced to 58% to 86% in its presence. The use of labelled nitrogen fertilizer permitted to estimate the recovery of 78 to 100% of the total nitrogen supplied to the soil-plant system. The incorporation of vermiculite in the soil decreased the amount of labelled nitrogen recovered, because the nitrogen fixed by vermiculite could not have been totally extracted in the determination of the soil total nitrogen. Water stress also decreased that amount by favoring the volatilization losses.